Recent development of mass spectrometry and proteomics applications in identification and typing of bacteria. Issue 4 (2nd February 2016) - Cheng, Keding; Chui, Huixia; Domish, Larissa; Hernandez, Drexler; Wang, Gehua
Abstract : Identification and typing of bacteria occupy a large fraction of time and work in clinical microbiology laboratories. With the certification of some MS platforms in recent years, more applications and tests of MS‐based diagnosis methods for bacteria identification and typing have been created, not only on well‐accepted MALDI‐TOF‐MS‐based fingerprint matches, but also on solving the insufficiencies of MALDI‐TOF‐MS‐based platforms and advancing the technology to areas such as targeted MS identification and typing of bacteria, bacterial toxin identification, antibiotics susceptibility/resistance tests, and MS‐based diagnostic method development on unique bacteria such as Clostridium and Mycobacteria . This review summarizes the recent development in MS platforms and applications in bacteria identification and typing of common pathogenic bacteria.